Sex-specific difference for melanoma from immunotherapy advancement - Li, Qianqian; Dong, Ying; Ma, Yujiao; Mo, You; Yuan, Jupeng (Frontiers in Oncology, 2024)
BackgroundThe evaluation of melanoma incidence and mortality trends based on population characteristics, with a particular focus on sex differences, is of utmost importance.MethodsThe gender-stratified analysis of melanoma mortality across various calendar years was conducted. Utilizing the Joinpoint software, we detected alterations in the incidence rates and delineated the mortality trends.ResultsMelanoma’s incidence-based mortality exhibited a rising trajectory between 2005 and 2010, characterized by an annual percent change (APC) of 2.95%. However, there was a significant decrease in mortality from 2015 to 2019, with an APC of -4.39%. Notably, the mortality among men decreased by about 5.84% between 2015 and 2019, while there was no significant downward trend in the mortality rate among women. Subsequent analysis revealed no statistically significant variation in the 2-year survival rate of female patients aged 45-54 years among different age groups (Z=-0.775, p >0.1).ConclusionsBetween 2015 and 2019, against the backdrop of stable melanoma incidence rates in the United States, there was a significant decline in mortality. Our analysis suggests that the utilization of immunotherapy may account for the observed reduction in mortality, with particularly notable benefits for male patients. However, female patients, especially younger women, did not derive significant advantages.